Research Trends of Creative Thinking in Education: Bibliometric Analysis 2016–2025 - F. Shoufika Hilyana; Dwi Yulianti; Ani Rusilowati; Bambang Subali (Yayasan Keluarga Guru Mandiri, 2026)
Creative thinking is an essential skill of the 21st century, seen as essential for the development of individuals, society, and the global workforce. This study aims to map the research landscape of creative thinking in education during the period 2016–2025 through a data-based bibliometric analysis of Scopus data. By applying the keywords